2002
DOI: 10.1023/a:1021546630577
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Thalidomide, an angiogenesis inhibitor is currently used in clinical trials in the US and Europe in combination with chemotherapy for the treatment of various solid tumors. The prognosis of patients suffering from small-cell lung cancer (SCLC) is poor. A 73-year-old female with extensive disease of SCLC was given six courses of chemotherapy with adriamycine, cyclophasphamide and oncovine, which led to complete remission of the disease. Following written informed consent, the patient has been treated with thali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…underlining the possible role of angiogenesis inhibitors in combination with traditional chemotherapy in the SCLC(35). A phase II trial evaluated thalidomide as maintenance therapy in 30 patients with ES-SCLC who had received first-line chemotherapy without progression disease(36).…”
mentioning
confidence: 99%
“…underlining the possible role of angiogenesis inhibitors in combination with traditional chemotherapy in the SCLC(35). A phase II trial evaluated thalidomide as maintenance therapy in 30 patients with ES-SCLC who had received first-line chemotherapy without progression disease(36).…”
mentioning
confidence: 99%
“…Mall et al reported a long-term survival in an SCLC patient after administration of thalidomide and combination chemotherapy 22. A phase II study assessing thalidomide as maintenance therapy in extensive-stage SCLC after response to chemotherapy showed that thalidomide has acceptable side effects 23.…”
Section: Thalidomidementioning
confidence: 99%